Documenting change across time: longitudinal and cross-sectional CA studies of classroom interaction - Pekarek Doehler, Simona; Fasel Lauzon, Virginie (Hoboken, New Jersey: Wiley-Blackwell, 2015)
The classroom as a site of learning has been the focus of research stemming from a large variety of theoretical backgrounds. The unique feature of conversation analytic (CA) classroom studies is that these document the accountable methods that members use to participate in social interactions within the classroom, thereby showing how factors such as motivation or competence emerge in and through the detailed unfolding of interaction. In this paper, we present current CA research on classroom interaction concerned with documenting change across time at different levels of granularity. We first discuss studies investigating change across short time-spans (minutes, seconds) and then turn to work documenting change across longer time-spans, based on longitudinal or cross-sectional designs. CA studies of classroom interaction that document change over time are most prominently concerned with the development of interactional competence (in a first or a second language). We show that existing findings support an understanding of the development of interactional competence as comprising speakers’ increased ability to deal with issues such as recipient design and preference organization, thereby enabling speakers to better tailor their turns and actions to fit the displayed expectations, needs and states of knowledge of co-participants.
Keywords: Applied linguistics; Conversation analysis; Educational linguistics; Language acquisition; Language and social interaction; Language in the classroom; Second language acquisition